A case study on the effect of cardinal directions on human inner energy / Hengameh Fazeli - Hengameh, Fazeli (2019)
For several centuries it was believed that architecture has a direct influence on the physical and psychological health of the users, through affecting the energy field around the body. Therefore many rules and patterns were established in traditional societies based on the experiences of generations dealing with the built space, including Feng Shui. Although the existence and properties of this energy field is scientifically proven in the fields of complementary sciences, medicine and biology, it is not being widely discussed in the field of architecture. The Feng Shui still to be seen as superstition. The concept of cardinal directions and directional energies, as one of the main concepts of Feng Shui, has been influential in determining the direction of the main door, windows and placement of furniture inside the house. The belief implies that auspicious directions promote health, while the inauspicious directions bring bad luck and disease. This research, has employed a sequential mixed-methods approach using Acugraph and Pranic Scanning, to measure the size of the energy field around the body, and explore the reason behind auspiciousness of the cardinal directions in Feng Shui. And to further examine if the impact of these directions are objective or affected by subjective matters. The result of experiments on 40 participants with various cultures, background and religion showed that cardinal directions have impact on the size of the aura and activation level of the energy centers. North and East direction increase the size of the aura and therefore have been considered auspicious while South and West decrease the size of the Aura and cause weakness. The results further showed that this influence is objective and is not affected by subjective matters. The study suggests that determining building direction has a significant impact to its users and the designer should be careful when dealing with the building orientation.